Post-analytical Error in Fatal Post-Cesarean Necrotizing Fasciitis and Sepsis: A Case Study. - WESLEY WILLIAMSON, THOMAS; KENWRIGHT, KATHLEEN M.; WILLIFORD PIFER, LINDA L. (Clinical Laboratory Science)
This is a case study of a 28 year old morbidly obese pregnant female with severe pre-eclampsia. She delivered at 32 weeks gestation by emergency cesarean section, and was discharged at three days post-surgery. The patient developed sepsis secondary to necrotizing fasciitis. She had been released from the hospital without her final complete blood count (CBC) having been reviewed by the attending physician, although it had been available for approximately 24 hours prior to her departure. The final CBC contained persuasive data suggesting that an adverse outcome could be highly probable. Discussion as to how this ultimately lethal post-analytic error might have been avoided, and perhaps prevented in the future is undertaken.